For all time : a Nantucket brides novel - Deveraux, Jude (Deveraux, Jude. Nantucket Brides, 2014)
"The wedding of Alix Madsen and Jared Kingsley is a glorious affair at an elegant little chapel in the woods. While most guests are fixed on the happy couple, Jared's cousin Graydon can't look away from bridesmaid Toby Wyndam. It's not just her quiet beauty that enthralls him. Toby possesses the remarkable ability of being able to distinguish Graydon from his identical twin. And according to family legend, that gift marks her as Graydon's True Love" --